KONDISI TATA KELOLA HUTAN UNTUK IMPLEMENTASI PENGURANGAN EMISI DARI DEFORESTASI DAN DEGRADASI HUTAN (REDD+) DI INDONESIA - Sulistya Ekawati; Mega Lugina; Kirsfianti L. Ginoga (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
One critical element for the success of REDD+implementation is its governance. The study aims to identify and analyze the existing REDD+ institutions from good governance point of view. The study are located in Central Lombok and Berau Districts, where REDD+ Demontration Activities already existed. In general, the study used qualitative methods, supported with scoring methode. The results show that REDD+ institutions have not fully reflected the three pillars of good governance, that there are still lack of community representation. Indicator of professionalism is at the highest score, while the indicator of participation is at the lowestscore. The institutions also have notapplied the principles of good governance yet. Allexisting REDD+ institutions are still temporary, that didn't represent a learning organization and tends overlapping functions. The research suggests several things: (i) Strengthening forest governance on the existing REDD+ institution carried out through strengthening the pillars of society and strengthening the principles of participation, (ii) Involvement of the communities should be enhanced in the institutional structure of REDD, (iii) Comprehensive assessment of the principles of good governance in the REDD+ institution at implementation stage that include payment distribution mechanism for emission reduction activities already undertaken, (iv) The function of the facilitate needs to be strengthened and (v) The structure institutions follow a REDD + strategies.